OVERSTATING VALUES: MEDICAL FACTS, DIVERSE VALUES, BIOETHICS AND VALUES-BASED MEDICINE - Parker, Malcolm (2013)
Fulford has argued that (1) the medical concepts illness, disease and dysfunction are inescapably evaluative terms, (2) illness is conceptually prior to disease, and (3) a model conforming to (2) has greater explanatory power and practical utility than the conventional value-free medical model. This ‘reverse’ model employs Hare's distinction between description and evaluation, and the sliding relationship between descriptive and evaluative meaning. Fulford's derivative ‘Values Based Medicine’ (VBM) readjusts the imbalance between the predominance of facts over values in medicine. VBM allegedly responds to the increased choices made available by, inter alia, the progress of medical science itself. VBM attributes appropriate status to evaluative meaning, where strong consensus about descriptive meaning is lacking. According to Fulford, quasi-legal bioethics, while it can be retained as a kind of deliberative framework, is outcome-based and pursues ‘the right answer’, while VBM approximates a democratic, process-oriented method for dealing with diverse values, in partnership with necessary contributions from evidence-based medicine (EBM). I support the non-cognitivist underpinnings of VBM, and its emphasis on the importance of values in medicine. But VBM overstates the complexity and diversity of values, misrepresents EBM and VBM as responses to scientific and evaluative complexity, and mistakenly depicts ‘quasi-legal bioethics’ as a space of settled descriptive meaning. Bioethical reasoning can expose strategies that attempt to reduce authentic values to scientific facts, illustrating that VBM provides no advantage over bioethics in delineating the connections between facts and values in medicine.
Keywords: values-based medicine; Values; Illness; facts; Disease; Bioethics